DRYING OF VIRGIN COCONUT OIL FROM FERMENTATION PROCESS USING DRY AIR METHOD - SAMSUDDIN, NUR EZZATU NISWAN (IRC, 2017)
The primary purpose of this project is to produce Virgin Coconut Oil (VCO) with lowest amount of moisture content possible. VCO is known for its antioxidants, pleasant aroma and taste, Medium Chain of Fatty Acid (MCFA) and vitamins. The commercial VCO produced from fermentation method may have water content with range from 0.10-0.42%. This high moisture content may shorten the VCO shelf life, change the color and will make the oil become rancid. However performing drying after fermentation at low temperature might help to overcome this issue. This experiment have been conducted by using drying oven to study the effect of drying temperature, drying time, surface area/ volume and also fermentation end time on moisture content. The moisture content will then be calculated by using the standard AOAC method. It was found that from 24 hour fermentation end time, by using drying temperature of 40°C with drying time about 150 minutes will produce the lowest moisture content of VCO with moisture content of 0.19%. In short, if this project is successfully executed, it will give numerous advantage to our local industry itself